Extracellular and membrane-derived nanovesicles from tumor cells as nanocarriers for immunomodulatory agents delivery - Quitiba, João Victor Brandão (2024)
Hepatocellular carcinoma (HCC) is among the neoplasms with the highest number of deaths worldwide, and the high frequency of recurrence and metastasis requires the development of new therapeutic proposals. Among them, small interfering RNA (siRNA) therapy offers a targeted strategy to silencing specific genes involved in cancer progression, potentially improving treatment efficacy and reducing the frequent side effects in traditional therapies. However, the instability and delivery challenges of siRNA hinder their clinical application. Biomimetic nanocarriers represent a promising technique to improving cancer treatment by enhancing stability and efficacy of therapeutic molecules, targeting their activity to tumor cells and immune cells, improving biocompatibility and immunogenicity with minimal toxicity. Here, we developed biomimetic nanovesicles (NVs) composed of extracellular vesicles and the main components of plasma membranes from HCC (HEP-G2) cells to deliver PD-L1 siRNA and tumor antigens to enhance anti-tumor immune responses and improve the immunogenicity of hepatocellular carcinoma cells. The membrane-derived nanovesicles (MNVs) and extracellular nanovesicles (ENVs) derived from HEP-G2 cells encapsulating polyethylenimine (PEI)-siRNA complexes showed a size distribution ranging from 100 nm to 200 nm, within the optimal size range for cellular uptake. Additionally, mathematical modeling considering surface ligands, concentration, and receptors concentrations revealed successful engineering of the NVs with a size that improves circulation time and surface properties that allow good stability and homotypic targeting to tumor cells, supporting their potential for targeted drug delivery. Our results demonstrated that membranederived nanovesicles (MNVs) exhibit higher interaction with tumor cells compared to extracellular nanovesicles (ENVs). NVs exhibit biocompatibility and effectively deliver PD-L1 siRNA and tumor antigens to immunocompetent and HCC cells, inducing significant phenotypic changes. Overall, these findings suggest that these NVs can effectively modulate immune responses and increase the immunogenicity of HCC cells, offering new alternatives for therapeutic intervention. Further research and clinical trials are needed to validate these results and explore the full potential of biomimetic NVs in cancer therapy.